2022
DOI: 10.3390/diabetology3010011
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Retinopathy: An Overview on Mechanisms, Pathophysiology and Pharmacotherapy

Abstract: Diabetes mellitus is one of the most frequently occurring metabolic disorders (DMs), impairing healthy life around the globe, with mild-to-severe secondary complications. DM is associated with secondary complications, including diabetic retinopathy (DR), which damages the retina and can lead to vision loss. Diabetic patients often suffer from extreme retinal capillary aneurysms, hemorrhage, and edema, which is likely to lead to non-proliferative or proliferative diabetic retinopathy (NPDR or PDR) and diabetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 81 publications
1
18
0
8
Order By: Relevance
“…Diabetes is one of the most prevalent pathological conditions affecting healthy living globally and is accompanied by multiple side effects [60]. It is reported that Diabetes mellitus is frequent in both the elderly and the young population [61].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes is one of the most prevalent pathological conditions affecting healthy living globally and is accompanied by multiple side effects [60]. It is reported that Diabetes mellitus is frequent in both the elderly and the young population [61].…”
Section: Discussionmentioning
confidence: 99%
“…These events are observed in hypertension, obesity, aging, and other disease conditions with retinopathy. Moreover, it alters the physiology of retinal blood vessels due to the development of ischemia and hypoxic events [52]. Furthermore, it causes visual field defects in the affected eye or both eyes [53].…”
Section: Discussionmentioning
confidence: 99%
“…As people's living standards improve and their dietary habits change, the incidence of diabetes and its associated complications has increased significantly. Among these complications, diabetic retinopathy (DR) is the most prevalent microvascular complication and a leading cause of visual impairment in the working-age population (44,45). DR can be classified into non-proliferative diabetic retinopathy (NPDR) and proliferative diabetic retinopathy (PDR) based on the severity of retinal lesions.…”
Section: Adma and Diabetic Retinopathymentioning
confidence: 99%